2005
DOI: 10.1007/s00405-004-0910-1
|View full text |Cite
|
Sign up to set email alerts
|

Angiofibroma: an outcome review of conventional surgical approaches

Abstract: Juvenile nasopharyngeal angiofibroma (JNA) is a benign tumor of the nasopharynx, and for its treatment, many surgical approaches have been recommended. However, selecting the appropriate one for the tumor in an advanced stage is still controversial. In this study, we evaluate the rate of recurrence of JNA and its relationship to the preoperative stage as well as various surgical approaches. Thirty-seven patients with pathologically proven JNA were retrospectively analyzed. For each patient, data were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
23
1
1
Order By: Relevance
“…[24][25] In most cases, the clinical presentation of the angiofibroma comprises the triad nose block, epistaxis, and a nasopharyngeal mass, which was similar to our findings in the study and in previously published papers. 13,14,26,27 The diagnosis of angiofibroma is given based on the clinical history, the physical examination, and nasal endoscopy; imaging studies, such as computed tomography, may add further information, as was done in the patients comprising this study. The correlation between preoperative staging based on computed tomography and the Fisch criteria 11 was possible in the 16 cases of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25] In most cases, the clinical presentation of the angiofibroma comprises the triad nose block, epistaxis, and a nasopharyngeal mass, which was similar to our findings in the study and in previously published papers. 13,14,26,27 The diagnosis of angiofibroma is given based on the clinical history, the physical examination, and nasal endoscopy; imaging studies, such as computed tomography, may add further information, as was done in the patients comprising this study. The correlation between preoperative staging based on computed tomography and the Fisch criteria 11 was possible in the 16 cases of this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the present study, all patients were male, and the mean age at the time of diagnosis was 16.8 years, which is similar to other published studies. [13][14][15]20,23 Genetic studies have demonstrated a close relation between these angiomas and androgen receptor expression, suggesting that this tumor is androgen-dependent. This could explain why the prevalence is higher in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is considered a benign neoplasm, this tumor is not encapsulated, may lead to local destruction and has high relapse rates1. This vascular tumor emerges mainly from the sphenopalatine foramen and may extend all the way to the middle cranial fossa 3,4 . According to the scheme proposed by Fisch 5 , these tumors may be contained within the nasal cavity and nasopharynx (I), invade the face sinuses or the pterygopalatine fossa (II), expand towards the infratemporal fossa, orbit, and parasellar region (III) or present intracranial invasion (IV).…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative bleeding may occur in any of the approaches and has been one of the main perioperative complications. Preoperative arterial embolization has been used systematically to reduce the amount of bleeding and the use of blood byproducts during surgery with good results 4,7 . However, there is no consensus as to the routine use of preoperative embolization, given its high cost and inconsistent availability of the procedure in care centers.…”
Section: Introductionmentioning
confidence: 99%